Disciplinary and generic variation of citation use in research articles - Qun Zheng; Bingyu Li (International Journal of English for Academic Purposes)
For novice writers as well as EAP practitioners, citation use poses considerable challenges stemming from the writers’ limited understanding of disciplinary conventions, unwarranted source use, or rhetorical strategies. Although studies handling those challenges have reported typical citation functions in various disciplines, the explanation of functions in terms of content still confuses novice writers. Citation content per se is crucial to the specificity and reliability of the evidence presented. Drawing on a form-content-function integration, the present study examined the Introduction and the Results and Discussion sections in sixty research articles from physics, biology, education, and applied linguistics. We found that non-integral citations prevail across the four disciplines. We also found variations of citation contents and functions in the four disciplines and in part-genres. Specifying rhetorical functions and content in part-genres can thus enhance the evaluative power of source use.